2009
DOI: 10.1021/ja902116f
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-free Preparation of Melamine-Based Microporous Polymer Networks through Schiff Base Chemistry

Abstract: Recently, the synthesis of organic materials with high porosity has received considerable scientific interest, and various chemical approaches have been applied to the build-up of microporous polymer networks. In a novel catalyst-free process using Schiff base chemistry, melamine has been reacted with various di- and trivalent aldehydes to form a series of highly cross-linked microporous aminal networks with BET surface areas as high as 1377 m(2)/g and a NLDFT micropore volume of up to 0.41 cm(3)/g. It was sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
481
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 627 publications
(509 citation statements)
references
References 19 publications
25
481
0
3
Order By: Relevance
“…Owing to the presence of an electron-deficient carbon atom, CO 2 is expected to interact with protic electronegative functionalities (for example, amines) leading to a strong chemisorption, while N 2 remains impartial. So far, this simple interaction has led to a plethora of nanoporous polymers where the nitrogen-rich functionalities, such as triazine 1,18 , tetrazole 3 , imidazole 41 , phosphazene 24 , imide 42 and amines 25,43 , are built in. In all these and many other situations 2 , CO 2 -philicity is the main driving force for the CO 2 /N 2 selectivity, without taking into account any chemical architecture that would repel N 2 molecules selectively.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the presence of an electron-deficient carbon atom, CO 2 is expected to interact with protic electronegative functionalities (for example, amines) leading to a strong chemisorption, while N 2 remains impartial. So far, this simple interaction has led to a plethora of nanoporous polymers where the nitrogen-rich functionalities, such as triazine 1,18 , tetrazole 3 , imidazole 41 , phosphazene 24 , imide 42 and amines 25,43 , are built in. In all these and many other situations 2 , CO 2 -philicity is the main driving force for the CO 2 /N 2 selectivity, without taking into account any chemical architecture that would repel N 2 molecules selectively.…”
Section: Synthesismentioning
confidence: 99%
“…These mostly organic polymers can easily be designed and constructed via facile synthetic protocols. To date, several crystalline and amorphous nanoporous organic materials with tunable functionality have been developed-namely, COF 14 , PIM 15 , HCP and CMP 16,17 , CTF 18 , PAF 19 , PPN 20 , POF 21 , BILP 22 , EOF 23 , PECONF 24 and COP 25 .…”
mentioning
confidence: 99%
“…3%) occurred at 440 °C in N2 and at 420 °C in air. These results indicate that COP-BIP is more stable than other covalent organic polymers such as triazine-based frameworks (about 410 °C in air) [20], melamine-based polymer (about 400 °C in N2) [8], COF-LZU1 (about 310 °C in N2) [2], and POFs (about 400 °C in N2) [10]. By comparison, a polymer with a N,O,N unit [21], which is different to the N,N,N unit of COP-BIP, is stable at 300 °C in N2.…”
Section: Resultsmentioning
confidence: 92%
“…The successful design and synthesis of these polymers linked by B-O [3][4][5], C-C [6,7], C-N [8], and C=N [9][10][11][12] bonds have been reported. Recent studies have shown that conjugated organic polymers (COPs) with extended π-conjugation possess high thermal stability and structure diversity [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…A well-defined Co-doped carbonitride framework (i.e., CoCN) was prepared first following a modified method [36]. In brief, melamine was reacted with terephthalaldehyde at the presence of trace cobalt nitrate via a one-step polycondensation reaction.…”
Section: Resultsmentioning
confidence: 99%